End-of-life experiences and deathbed phenomena as reported by Brazilian healthcare professionals in different healthcare settings. Issue 4 (28th November 2016) - Santos, Claudia Soares Dos; Paiva, Bianca Sakamoto Ribeiro; Lucchetti, Alessandra Lamas Granero; Paiva, Carlos Eduardo; Fenwick, Peter; Lucchetti, Giancarlo
ABSTRACT: Objective: The objectives of the present study were to describe and compare the characteristics and reports of end-of-life experiences (ELEs) by healthcare professionals at different institutions and to investigate the influence of religious beliefs on these reports. Method: A multicenter study was carried out in Brazil that included six nursing homes (NHs), a cancer hospital (ONC), and a palliative care (PC) unit. Sociodemographic data, ELE reports (Fenwick's questionnaire), religiosity (the Duke Religion Index), spirituality (the Spirituality Self-Rating Scale), and mental health (the DASS-21 questionnaire) were assessed. The analysis was performed using ANOVA and chi-square tests in order to compare ELE perceptions in these different settings. Results: A total of 133 healthcare professionals (46 ONC, 36 PC, and 51 NH) were interviewed, 70% of whom recounted at least one ELE report in the previous five years. The most common ELEs were "visions of dead relatives collecting the dying person" (88.2%), "a desire to mend family rifts" (84.9%), and "visions of dead relatives near the bed providing emotional comfort" (80.6%). Most healthcare professionals (70–80%) believed that these experiences had a spiritual significance and were not due to biological effects. Comparison among settings revealed that those working in the PC unit had more reports, a greater openness about the issue, and more interest in training. Individual religious beliefs had no influence on perception of ELEs. Significance of Results: Our study revealed that ELE reports are not uncommon in clinical practice and seem to be little influenced by religious or spiritual beliefs. Although strongly reported in all settings, palliative care professionals tend to be more open to this issue and have a stronger perception of ELEs.